(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
This paper explores the elastic coefficient of sponge material in different functional areas and functional zones of the bra mold cup to improve the accuracy of parameter setting in the finite element modeling of the bra mold cup, reduce the error of simulation experiment results, and provide more theoretical basis and data reference for functional research direction in the design and production process of the bra mold cup. In this paper, three converging bra mold cups of the same style and size are selected as samples, and the mold cups are divided into three measuring areas according to functional zones. Eight measuring points are selected, and micrometer and air bag contact pressure measuring system are used to measure the wearing pressure of each measuring point and the corresponding pressure of each measuring point when compressed every 0.2 mm. Excel software was used for linear fitting of data to obtain the range of elastic coefficients and elastic distribution of different functional regions of the bra cup. At the same time, this method can also be used to analyze the wearing pressure and elastic distribution of other types of bra mold cups, providing more research reference direction and technical basis for the design and production of bra molds cups.